The Use of Simulated Patients Is more Effective than Student Role Playing in Fostering Patient-Centred Attitudes during Communication Skills Training: A Mixed Method Study. (17th December 2022) - Gorski, Stanislaw; Prokop-Dorner, Anna; Pers, Michal; Stalmach-Przygoda, Agata; Malecki, Łukasz; Cebula, Grzegorz; Bombeke, Katrien
Abstract : Objective . While simulated patients (SPs) are considered a standard tool in communication skills training, there is no evidence thus far of their comparative benefit to the more cost-effective option of student role playing. We compared the effectiveness of both approaches in developing patient-centred attitudes in students. Methods . We retrospectively compared students who participated in the clinical communication course (CCC), based on student role playing (CCCsp-, n = 160 ), to students who participated in the CCC with SPs (CCCsp+, n = 146 ), and students with no formal CCC (CCC-, n = 122 ). We used validated questionnaires to assess patient centredness. We also conducted focus group interviews (FGI) to better understand the impact of CCC with sp. Results . Students after the CCC with simulated patients achieved a significantly higher score in the patient-practitioner orientation scale than other groups (p < 0.001 ). Conclusions. There is a strong positive correlation between the implementation of simulated patients and patient-centred attitudes among students. Data from the FGI revealed that students perceived training with SP as more realistic, safe, and engaging than student role playing. Practice Implications . Our research provides evidence to justify costs and resources invested in simulated patient programs.